Традиційне харчування волинян - Давидюк, М. (Народна творчість та етнографія, 2006)
The author suggests the continuation of the article researching traditional eating habits of the settlers of Volyn. This part offers some notes on meals from fish, soft and alcoholic drinks. Religious food, its peculiarities and importance are described in the article. Food cooked for religious holidays bears a strong symbolic message that overwhelms its practical functions. A thorough research is given to food made for birth and baptizing of the child, wedding and funeral. Traditional food for holidays of each season (such as Christmas, Easter, etc.) and observances connected with them are illustrated brightly.